Structural health monitoring: An orthopaedic perspective. (September 2015) - Wong, Lydia CY; Chiu, Wing K; Russ, Matthias; Liew, Susan M; Ilahee, Nabil A
Having unstable sacral fractures requires patients to be bedridden for a significant period of time for healing to take place without complications. This causes severe muscle atrophy, along with blood circulation problems in older patients. It is therefore highly beneficial to fast-track weight-bearing activities to reduce these complications by monitoring the recovery of the fracture. Past experimental work shows that dynamic response of a fixated synthetic (fourth-generation composite sawbone) pelvis is affected by the change in stiffness at the fracture location. The changes in this dynamic response can be observed by placing sensors on the pelvis and on the fixation. However, placing sensors on the pelvis is not practical. The aim of this article is to report on a set of computational investigation on the potential of placing sensors on the fixation to determine the stiffness restoration of the fractured region of the pelvis. This work will focus on the Denis I fracture, where the fracture is located in the sacrum. The ability to relate the dynamic response of a particular section of the fixation that is remote to the fracture location will have significant implication in the extending structural health monitoring concept to determine the state of healing of a fractured pelvis. A fourth-generation composite sawbone pelvis was used in the work reported in this article.